The social media Infodemic of health-related misinformation and technical solutions - Flinta, Rodrigues (2024)
This paper discusses the role of social media algorithms in the spread of misinformation during the COVID-19 pandemic. It aims to propose solutions to combat misinformation and promote accurate, evidence-based public health information.